2004
DOI: 10.1029/2003jb002516
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric structure of the Yukon, northern Canadian Cordillera, obtained from magnetotelluric data

Abstract: [1] Two goals of Lithoprobe's geoscientific studies in the Phanerozoic accretionary cordillera of western North America were to define the subsurface geometries of the terranes and to infer the physical conditions of the crust. These questions were addressed in Canada's southern cordillera a decade ago and have more recently been addressed in the northern cordillera, of which one component of the new studies is magnetotelluric (MT) profiling from ancestral North American rocks to the coast. We present a resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 76 publications
(119 reference statements)
3
46
0
1
Order By: Relevance
“…The output of the sensitivity values is the sum of the squares of each column and represent the sum over all the data (stations and frequencies) (Rodi and Mackie, 2001). In this study, the structures with sensitivity matrix values >0.0001 were con- sidered to be resolved features, which is in agreement with other recent works, such as those by Brasse et al (2002) and Ledo et al (2004). Most of the Chinchpada-Godhra profile shows (Fig.…”
Section: Magnetotelluric Data and Methodologysupporting
confidence: 79%
“…The output of the sensitivity values is the sum of the squares of each column and represent the sum over all the data (stations and frequencies) (Rodi and Mackie, 2001). In this study, the structures with sensitivity matrix values >0.0001 were con- sidered to be resolved features, which is in agreement with other recent works, such as those by Brasse et al (2002) and Ledo et al (2004). Most of the Chinchpada-Godhra profile shows (Fig.…”
Section: Magnetotelluric Data and Methodologysupporting
confidence: 79%
“…Deformation and metamorphism of ocean lithosphere containing a fluid phase can disperse carbon (Mareschal et al 1992), and enhanced conductivity is observed in continental crust above presently actively subducting plates such as above the Juan de Fuca plate in Oregon, Washington, and southern British Columbia (Wannamaker et al 1989;Kurtz et al 1990; see also Jones 1993). In SNORCLE corridors 2 and 3 in the northern Cordillera (Yukon and northern British Columbia), a conductive anomaly is observed in a region in which subduction ceased at 40 Ma and is, therefore, attributed to a mineralogical constituent created by the subduction process rather than remnant fluid or thermal sources (Wennberg et al 2002;Ledo et al 2003). It is of note that the deformation associated with the Fort Simpson -Hottah collision involved significant fluid movement and subsequent melting of continental crust as indicated by the presence of calc-alkaline magmatism in the Fort Simpson magmatic arc.…”
Section: Fort Simpson -Hottah Conductormentioning
confidence: 96%
“…The moderate velocities to the east appear to correlate with the Middle and Late Cretaceous(?) Deadman Creek batholith (Gordey et al 1998) as do high conductivities (Ledo et al 2004). The thickest near-surface section of low-velocity (<4.3 km/s) rocks occurs between the fault traces and beneath the Teslin River valley.…”
Section: Seismic Datamentioning
confidence: 97%